COMPARISON OF RICE FARMING INCOME WITH CORN AND WATERMELON FARMING IN SUBAK PANGYANGAN PANGYANGAN VILLAGE, PEKUTATAN DISTRICT - Ni Luh Putu Sindi Asih; Made Antara; Gede Mekse Korri Arisena (Agribusiness Journal, 2022)
Subak Pangyangan is one of the subaks that still rely on the cultivation of food crops to lift their family's economy, where rice plants are still a food crop that is widely cultivated compared to other crops including corn and watermelon, so the corn and watermelon plants in Subak Pangyangan are Opoortunity Cost or "cost" (as a lost benefit) of the product after making a choice. . The purpose of the study is: 1) analyzing the comparison of rice farming income with opportunity cost (corn and watermelon).   2) describe the obstacles faced by rice, corn and watermelon farmers in Subak Pangyangan, Pangyangan Village, Pekutatan District.  Sample collection is used census method that uses the entire population as a research sample. The first goal is analyzed with business income analysis, R/C ratio analysis and one-way anova test to find out the average revenue breakdown using SPSS 25 software, while the second goal is with descriptive analysis methods. The results of the study showed: 1) there is an average difference in nominal terms between the income of rice, corn and watermelon farmers per hectare in one growing season where each agricultural income is Rp 9.510.234.00, corn farming income of Rp 40,895,631.00, and watermelon farming income of Rp 32,526,710.00.  The lowest rice R/C ratio among the three types of farming is 2.00, while corn is 5.45 and watermelon is 2.82.  Statistical tests showed a marked difference between the three types of farming at a level of 5%.  The obstacles faced by farmers include an uncertain climate, pest and disease attacks, price changes, finance / capital and marketing. Keywords: income , rice farming, corn farming, watermelon farming, agricultural constraints